Penggunaan Dana Lembaga Ekonomi Desa (LED) dalam Meningkatkan Kesejahteraan dan Pemberdayaan Masyarakat Persfektif Maqasid Syariah (Studi Masyarakat Desa Sei Bamban, Kecamatan Batang Sarangan, Langkat) - Reni Dwijaya; Kamila K; Nursantri Yanti (Universitas Muhammadiyah Surabaya, 2023)
AbstractThis paper aims to see how the use of Sumber Rezeki Village Economic Institution (LED) funds in Sei Bamban Village, Batang Serangan District in increasing the welfare and empowerment of the community in the perspective of maqashid sharia, by conducting in-depth research using qualitative methods with a descriptive approach by extracting data sources through observation, interviews and documentation. Furthermore, data triangulation techniques were carried out at the stages of data reduction, data presentation, and drawing conclusions to see the validity of the data. The results of the study show that the funds lent by Sumber Rezeki LED are not in accordance with the values and principles of maqashid sharia. However, LED Sumber Rezeki's other actions are in accordance with the principles and values of maqashid sharia. Thereby increasing the welfare and empowerment of the people of Sei Bamban Village, Batang Serangan District.Keywords: Maqasid Sharia; Welfare and Empowerment; Village Economic Institution Fund (LED)